Influence of zero-burning policy and climate phenomena on ambient PM2.5 patterns and PAHs inhalation cancer risk during episodes of smoke haze in Northern Thailand - Nuttipon Yabueng (2020)
© 2020 Elsevier Ltd Air pollution from open burning in the Southeast Asian region has become an important environmental issue in the past decade, mainly due to its impacts on the economy and human health. Daily samples (24-h sampling) of particulate matter having an aerodynamic diameter equal to or less than 2.5 μm (PM2.5) were collected during the dry season (March–April) in the years 2017 and 2018 from two sampling sites: one in a suburban area of Chiang Mai Province (CM) that is regularly impacted by forest fires during the dry season, and one near an agricultural residue burning source located in Nan Province (NN). Daily average PM2.5 concentrations measured in Chiang Mai from both years (around 38–42 μg/m3) were about 2 times lower when compared to the same time period prior to the implementation of the zero-burning policy (2012–2015) with an average PM2.5 of 67.1 ± 34.1 μg/m3. Comparisons made during La Niña years (which are usually less affected by open burning), i.e. in 2012 (56 μg/m3), make it clear that a drop in PM2.5 values was influenced by the implementation of the zero-burning policy that was enforced for a period of about 60 days in an attempt to control open burning practices in upper Northern Thailand. Based on the patterns of PM2.5 concentrations observed during the dry season, it was determined that the policy could reduce open burning activities during the periods of the policy implementation. However, the zero-burning policy has also contributed to prolonging the smoke haze situation from a 2-month period (mid Feb –mid Apr) to a 3-month-long period (mid Feb–mid May). Moreover, health risks from the inhalation of PM2.5 bound PAHs is of great concern. PM2.5 concentrations at the two study sites were not significantly different, but average concentrations of 16 PAHs at the NN station for both years (̴ 5 ng/m3) were higher than those at the CM station (̴ 2 ng/m3). Therefore, exposure to PM2.5 at Nan area was more hazardous than at Chiang Mai. The ratio of some PAHs, i.e. BaA/(BaA + CHR) and IND/(IND + BPER), were used to determine the potential pollutant sources during the dry season, and it was found that PM2.5 at both sampling sites probably originated from similar source origins, i.e. wide-spread biomass burning (major source) and traffic emissions (minor source). In addition, not only are fine particulate matters a concern, but their chemical composition, particularly the levels of carcinogenic compounds that are bound to the PMs, are also believed to be a significant cause of these adverse health effects.